Profesionalisme Guru Madrasah Ibtida’iyah Dalam Mengimplementasikan Pembelajaran Berdiferensiasi Pada Kurikulum Merdeka - Munawir Munawir; Zulia Alfi Nur Aini; Sevtiyah Mubarokah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
This study examines the relationship between Madrasah Ibtidaiyah (MI) teacher professionalism and the effectiveness of differentiated instruction in implementing Kurikulum Merdeka through a Systematic Literature Review (SLR) approach based on PRISMA guidelines. From 187 initial articles searched through Google Scholar, ERIC, Scopus, and SINTA for the period 2015-2025, 20 studies were selected as primary sources. Data analysis employed open coding, axial coding, and selective coding with validation through source triangulation, audit trail, and peer debriefing. The research identified four main themes: (1) pedagogical competence as the dominant factor in differentiation quality; (2) weak diagnostic assessment as a link between professionalism and differentiation; (3) theory-practice gap and operational barriers; (4) Islamic tarbiyah dimension as a distinguishing factor yet underutilized. Findings reveal a structural paradox where 80% of teachers understand differentiation but only 35% implement it fully due to systemic barriers such as high administrative burden, limited ICT infrastructure, and minimal principal support. This study concludes that differentiation effectiveness in MI depends on three simultaneous conditions: madrasah structural support, continuous professional development, and integration of tarbiyah into technical competencies. Research limitations include the dominance of descriptive-exploratory studies without strong causal designs and limited geographical distribution in Java-Sulawesi, thus requiring longitudinal or mixed-methods research for deeper validation